Effect of three different antioxidants on the shear bond strength of composite resin to bleached enamel: An in vitro study - Subramonian, Rajalekshmy (J Conserv Dent, 2015)
OBJECTIVE: The effect of 10% sodium ascorbate, 10% grape seed extract, and 10% pine bark extract on the shear bond strength of composite resin to bleached enamel was evaluated. MATERIALS AND METHODS: Ninety recently extracted human premolars were divided into six groups of 15 teeth each. Except Group I (negative control), the labial enamel surface of all specimens in the other groups were bleached with 37.5% hydrogen peroxide. After bleaching, Group II specimens were stored in artificial saliva for 3weeks before composite bonding. Immediately following bleaching; Groups III, IV, and V specimens were treated with antioxidants 10% sodium ascorbate, 10% grape seed extract, and 10% pine bark extract, respectively, for 10 min and bonded with composite resin. In Group VI (positive control), the composite bonding was done immediately after bleaching. All specimens were stored in deionized water for 24 h at 37΀C before shear bond strength testing. The data obtained were tabulated and statistically analyzed using analysis of variance (ANOVA) and Duncan's multiple range test. RESULTS: The unbleached teeth showed the highest shear bond strength followed by the bleached teeth treated with the antioxidant 10% pine bark extract. CONCLUSION: Within the limitations of this study, it was observed that the use of antioxidants effectively reversed the compromised bond strength of bleached enamel. Among the antioxidants, 10% pine bark extract application after bleaching showed better bond strength.